2009
DOI: 10.1099/mic.0.027029-0
|View full text |Cite
|
Sign up to set email alerts
|

Transfer, stable maintenance and expression of the mycolactone polyketide megasynthase mls genes in a recombination-impaired Mycobacterium marinum

Abstract: The human pathogen Mycobacterium ulcerans produces a polyketide metabolite called mycolactone with potent immunomodulatory activity. M. ulcerans strain Agy99 has a 174 kb plasmid called pMUM001 with three large genes (mlsA1, 51 kb; mlsA2, 7.2 kb; mlsB, 43 kb) that encode type I polyketide synthases (PKS) required for the biosynthesis of mycolactone, as demonstrated by transposon mutagenesis. However, there have been no reports of transfer of the mls locus to another mycobacterium to demonstrate that these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
(42 reference statements)
2
15
0
Order By: Relevance
“…Similarly, we investigated DNA sequences upstream of mup045 and found a TSP at T207 with a potential SigA promoter element predicted by PoSSuM and confirmed by a loss of GFP expression in M. smegmatis following mutagenesis of the proposed −10 box. The principal mycobacterial sigma factor sigA is utilized by genes expressed during exponential growth [49], thus the data from mlsA/B and mup045 fit well with our previous report that show these genes are constantly expressed during exponential growth in the heterologous host, M. marinum [35].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, we investigated DNA sequences upstream of mup045 and found a TSP at T207 with a potential SigA promoter element predicted by PoSSuM and confirmed by a loss of GFP expression in M. smegmatis following mutagenesis of the proposed −10 box. The principal mycobacterial sigma factor sigA is utilized by genes expressed during exponential growth [49], thus the data from mlsA/B and mup045 fit well with our previous report that show these genes are constantly expressed during exponential growth in the heterologous host, M. marinum [35].…”
Section: Discussionsupporting
confidence: 82%
“…The constructs were confirmed to be correct in mycobacteria by Southern hybridization and back transformation to E. coli . Acetone soluble lipids were extracted from recombinant M. ulcerans and analysed by LC-MS for the presence of mycolactones as previously described [35].…”
Section: Methodsmentioning
confidence: 99%
“…Dormancy of the bacteria was estimated by quantifying the expression of devR, devS, and icl (27)(28)(29), and mycolactone biosynthesis gene expression, that is, mup053, mup045, mup038, mlsA1 (30)(31)(32), and KR (33), was also estimated. Analysis was performed utilizing the DDCt method with the ppk gene as housekeeping gene (34). Primer sequences are presented in Supplemental Fig.…”
Section: Quantitative Pcr Analysismentioning
confidence: 99%
“…M. marinum M and M. ulcerans 06-3844 (the latter isolate also referred to as M. marinum 06-3844) [25] were cultured at 30°C in 7H9 Middlebrook broth or 7H10 Middlebrook agar as described [12]. Antibiotics were used at the following final concentrations in mycobacteria: apramycin 50 μg/mL; kanamycin 25 μg/mL; and hygromycin 50 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has never been shown that these genes are sufficient for toxin synthesis. There is only one published report of an experiment to test sufficiency, with the transfer (in two parts) of the 174 kb pMUM001 plasmid that harbours the mls genes to Mycobacterium marinum , a natural producer of many polyketide metabolites and a very close relative of M. ulcerans [12]. This experiment showed that the mls genes were expressed in M. marinum but mycolactones were not detected [12].…”
Section: Introductionmentioning
confidence: 99%